Mix Codes on Tuah Kreasi Youtube Channel - Ritman Datu; Yunidar Yunidar; Arum Pujining Tyas; Juniati Juniati; Julia Marfuah (Civiliza Publishing, Indonesia., 2026)
Language is a communication tool that has an important role in human life as a social entity, especially in interacting and communicating. This study aims to describe the forms of code mixing and the factors that cause code mixing in the content of the YouTube channel tuah kreasi. This study uses a qualitative approach with a descriptive method. The research data is in the form of speech that contains mixed codes obtained from several videos on the YouTube channel Tuah Kreasi. The data collection technique is carried out through the observation and record method, while the data analysis technique uses the Miles and Huberman model which includes data condensation, data presentation, and conclusion drawn. The results of the study showed that twenty-eight code mixing data were found consisting of code mixes in the form of words, phrases, and clauses. The most dominant form of code mixing is mixing code at the word level as many as fourteen data, followed by mixing code at the phrase level as many as eleven data, and mixing code at the clause level as many as three data. The code mix found consists of mixing code in that involves regional languages and mixing code outside that involves foreign languages, namely English, Arabic, Javanese, and Korean. English is the most dominant language used with a total of twenty data, then Arabic five data, Javanese two data, and finally Korean one data. The factors that cause code mixing include speaker factors and linguistic factors. The most dominant factor is the linguistic factor with a total of eighteen data, because it relates to the need for speakers to convey meaning precisely, specifically, and efficiently, especially in the use of scientific, technical, and popular terms. Meanwhile, the speaker factor only amounted to ten data, because it was related to cultural background, language habits, social identity, and communication style of the speaker. Thus, the phenomenon of code mixing on the tuah kreasi youtube channel reflects the dynamics of language use in a bilingual society which is influenced by the development of social media and globalization.